Sophisticated Thinking: Higher Order Thinking Skills - Elena Tikhonova; Natalia Kudinova (National Research University Higher School of Economics, 2015)
The information-based society determines that the key factor to achieve success is the development of sophisticated thinking. That said, the thinking process cannot be just a mere imitation of cognitive work, since the digital age requires the authentic skills of working with a flow of information that is being constantly updated. This paper deals with the last stage of the study devoted to the development of sophisticated thinking. It focuses on the enhancement of higher order thinking skills. We claim that the cognitive processes should be based on three phases: development of disposition towards both thinking process and processed information; development of lower order thinking skills which serves as an indispensable basis for developing higher order thinking skills; and development of higher order thinking skills. The omission or reordering of any of these phases may result in significant deterioration of the obtained results. The special emphasis is put on the idea that higher order thinking skills are more effectively developed when lower order thinking skills have already been interiorized. Furthermore, the development of disposition is regarded as the cornerstone of the development of sophisticated thinking in general. Also, due to its defining feature of polysemy, a literary text is considered to be the most appropriate basis for enhancing students' thinking skills. For the purpose of verifying the theoretical ideas, a qualitative study has been conducted. The two groups of students, who participated in the first and second stages (three-month cycle each) of our project, continue to be involved in this one. They are second-year bachelor students of the Higher School of Economics who are studying English as a second language. On the basis of the ideas expressed by B. Bloom about the division between lower and higher order thinking skills and by J. Mezirow about transformative learning we designed tasks to enhance higher order thinking skills. These tasks were related to the short stories written by D. Barthelme and printed as a collection, Sixty Stories. To teach the students of both groups (control and experimental), the text-based approach with special techniques to measure the students' level of understanding and the ability to apply the given information was used. The results of the experiment indicated that the students of both groups made headway in their application of thinking skills. However, the students of the experimental group demonstrated a more significant shift due to the fact that the development of their disposition towards cognitive processes and processed information had been specifically targeted over the course of the first and second stages of the project. Another important outcome of the study was that the participants' frame of reference was extended which allows us to speculate that the development of sophisticated thinking may result in the change of a person's interpretation of socio-cultural situation. Hence, a further in-depth study of the issue should be conducted.